MAXIMUM COVERAGE MODEL IN FUNCTION OF OPTIMIZATION OF POLICE RESOURCES - Petrović, Jovan M (National interest, 2025)
Location problems are some of the fundamental issues when using police resources. Material and human resources are essential factors in the functioning of the police organization and are the basis for making decisions about the allocation of resources. The paper explores the possibilities of using the maximum coverage model when solving location problems, using GIS technologies as a means of decision support in the Police Directorate in Zrenjanin. The research is illustrated with practical examples, all with the aim of optimization and rational use (engagement) of the resources of the Police Directorate. The research findings answer the question of which locations police patrols should be deployed to be more efficient and effective in performing tasks such as combating crime and immediately depriving perpetrators of criminal acts of their freedom. The limitations of the paper relate to solving location problems in only one police department and using one software and method, as well as the lack of research concerning crime hotspots.